Cryptoporic and isocryptoporic acids from the fungal cultures of Polyporus arcularius and P. ciliatus - Cabrera, Gabriela Myriam (2002)
In a chemical study of several fungal cultures of Polyporus, a methyl ester of cryptoporic H was isolated from P. ciliatus, together with cryptoporic acid H and 5-hydroxymethylfuran-3-carboxylic acid. Furthermore, two additional compounds, named isocryptoporic acids H and I, were isolated from P. arcularius. These isocryptoporic acids are isomers of the cryptoporic acids with drimenol instead of albicanol as the terpenoid fragment; their structural elucidation was determined by application of spectroscopic methods.